Correlating quality of translation and organization of mental lexicons - Legutko-Marszałek, Iwona (Glottodidactica, 2018)
I have discussed cognitive aspects of translation and have attempted to pay particular attention to the cognitive conditions guaranteeing the correct process of translation. Translating from one language into another is, in my opinion, possible thanks to reference to the conceptual ground and information processing outside language. The division of a single mental lexicon common to two languages into two separate mental lexicons influences the quality of translation. The condition of a successful translation is the correct identification of the conceptual structure and this, in turn, is possible only after the division of the mental lexicons so that the lexical units have direct access to concepts beyond language and are able to activate them.